Reinterpretation Of The Hadith On Commercial Profit: A Ma'āni Al-Hadith Approach Toward Contemporary Islamic Business Ethics - Ali Muhayatsyah; Sjafruddin; Naizatul Afni (Journal of Contemporary Indonesian Islam, 2026)
Profit is an integral component of commercial transactions in Islam. Nevertheless, the hadith concerning commercial profit is frequently interpreted textually as legitimizing unlimited profit-taking, overlooking its ethical dimension and the objectives of Islamic law. This study aims to analyze the hadith on commercial profit using the Ma'āni al-Hadith approach and to examine its relevance to contemporary Islamic business practices. This research employed a qualitative library research method. The data were collected from primary hadith compilations concerning commercial profit, supported by classical hadith commentaries, Islamic commercial jurisprudence, Islamic economics literature, and relevant scholarly publications. The data was analyzed through takhrij al-hadith, sanad criticism, matn criticism, and contextual interpretation based on the Ma'āni al-Hadith approach. The findings reveal that Islam does not prescribe a fixed percentage of commercial profit; instead, it emphasizes that profit should be earned through honest, fair, transparent, and mutually consensual (tarāḍin) transactions while avoiding fraud (ghash), uncertainty (gharar), and monopoly (iḥtikār). The study further demonstrates that the universal values embedded in the hadith remain relevant to contemporary business practices by integrating the Ma'āni al-Hadith approach with maqāṣid al-sharī‘ah. This integration contributes to the development of contextual Islamic business ethics that promote justice, public welfare, and sustainable commercial practices.